Importance of offshore wind farms Marmara Sea for Turkey’s renewable energy targets: a case study Marmara Sea - Karipoğlu, Fatih (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In Turkey, current energy generations are not sufficient for the existing energy needs and besides, energy demand is expected to increase by 4-6% percent annually until 2023. Therefore, the government aims to increase the ratio of renewable energy sources in total installed capacity to 30 percent by 2023. Turkey has three quarter seas around itself. So, Turkey has a high level offshore wind potential for energy generations. But there are not any offshore wind farms in Turkey seas. In this study, we aimed at assessing the viability of establishing offshore wind farms of Marmara Sea and to identify favorable sites for such farms using Geographical Information System (GIS) procedures and algorithms. GIS layers were created and a weighted overlay GIS model based on the above mentioned criteria was built to identify suitable sites for hosting a new offshore wind farm. Furthermore, EMODnet (the European Marine Observation and Data Network) and GWA (Global Wind Atlas) were employed for data acquisition to unlock fragmented and hidden marine data resources and to facilitate investment in sustainable coastal and offshore activities. Received technical, social and environmental data from different sources were processed in the GIS and we created the GIS-based model. Results showed that most of Marmara Sea offshore areas were unsuitable. There are only two suitable areas. It is apparent that the growth of offshore wind farms in Turkey will increase provided that the supporting mechanism and the necessary legislation are ensured.